2016
DOI: 10.1038/srep38723
|View full text |Cite
|
Sign up to set email alerts
|

BIX01294, an inhibitor of histone methyltransferase, induces autophagy-dependent differentiation of glioma stem-like cells

Abstract: Glioblastoma (GBM) contains rare glioma stem-like cells (GSCs) with capacities of self-renewal, multi-lineage differentiation, and resistance to conventional therapy. Drug-induced differentiation of GSCs is recognized as a promising approach of anti-glioma therapy. Accumulating evidence suggests that unique properties of stem cells depend on autophagy. Here we demonstrate that BIX01294, an inhibitor of a G9a histone methyltransferase (introducing H3K9me2 and H3K27me3 repressive marks) triggers autophagy in hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
78
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(87 citation statements)
references
References 61 publications
(94 reference statements)
8
78
0
Order By: Relevance
“…The LN-18 cells also formed compact distinctive spheroids in hydrogel. Interestingly, previous studies have demonstrated the formation of neurospheres by LN-18 cells in the presence of growth factors [38]. These combined results are consistent with research that shows that the morphology of cells in culture is responsive to hydrogel environments [8, 9] and warrant future experiments examining the impact of serum-free media on cell growth in monolayer and hydrogel cultures [38, 39].…”
Section: Discussionsupporting
confidence: 84%
“…The LN-18 cells also formed compact distinctive spheroids in hydrogel. Interestingly, previous studies have demonstrated the formation of neurospheres by LN-18 cells in the presence of growth factors [38]. These combined results are consistent with research that shows that the morphology of cells in culture is responsive to hydrogel environments [8, 9] and warrant future experiments examining the impact of serum-free media on cell growth in monolayer and hydrogel cultures [38, 39].…”
Section: Discussionsupporting
confidence: 84%
“…A protein complex can be pulled down with one or two antibodies depending on whether only the interaction is a matter of interest, or the expression of the two individual proteins is being examined (18). In this case, Beclin-1 and EGFR are established as being expressed in LN18 cells (19,20). For that reason, co-immunoprecipitation was performed using Beclin-1 alone for pull-down.…”
Section: Co-immunoprecipitationmentioning
confidence: 99%
“…To validate experimentally the discovered regulatory link, we evaluated ANXA2R and FOXM1 expression levels in different glioma cells: LN18, LN229, U87 established glioma cell lines, patient-derived WG4, IPIN glioma cell cultures (Ciechomska et al, 2016) and normal human astrocytes (NHA) using quantitative PCR (qPCR). Relatively to normal human astrocytes, the expression of ANXA2R in those cells was elevated only in patient-derived WG4 glioma cells; while FOXM1 expression was significantly elevated in 4 out of 5 cell lines ( Figure 6H).…”
Section: Differential Activation Of Regulatory Regions Coupled With Cmentioning
confidence: 99%
“…Human malignant U-87 MG, LN18 and LN229 glioblastoma cells were purchased from American Type Culture Collection (ATCC). WG4 and IPIN are primary glioma cell lines developed from GBM patient surgical samples as described before (Ciechomska et al, 2016).…”
Section: Human Glioma Cell Linesmentioning
confidence: 99%